The Good and Bad of β-Catenin in Kidney Development and Renal Dysplasia - Boivin, Felix J.; Sarin, Sanjay; Evans, J. Colin; Bridgewater, Darren (Frontiers in Cell and Developmental Biology, 2015)
Congenital renal malformations are a major cause of childhood and adult onset chronic kidney disease. Identifying the etiology of these renal defects is often challenging since disruptions in the processes that drive kidney development can result from disruptions in environmental, genetic, or epigenetic cues. β-catenin is an intracellular molecule involved in cell adhesion, cell signaling, and regulation of gene transcription. It plays essential roles in kidney development and in the pathogenesis of renal dysplasia. Here, we review the function of β-catenin during kidney development and in the genesis of renal dysplasia.